2016
DOI: 10.1039/c5tc04402b
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetic anisotropy of a 5d transition metal decorated two-dimensional polyphthalocyanine framework

Abstract: Giant perpendicular magnetic anisotropy is found in a 5d transition-metal adatom decorated two dimensional (2D) polyphthalocyanine framework (TM@Pc) by means of first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…For other properties like magnetism which have been studied considerably, we refer the reader to existing literatures. 29,[52][53][54][55][56][57][58]…”
Section: Electron Localization In Typical Building Unitsmentioning
confidence: 99%
“…For other properties like magnetism which have been studied considerably, we refer the reader to existing literatures. 29,[52][53][54][55][56][57][58]…”
Section: Electron Localization In Typical Building Unitsmentioning
confidence: 99%
“…Unlike graphene, the symmetry of a single layer is not hexagonal, but rather D 4h . This unique structure makes 2D PPC highly promising material for a wide variety of technological applications, including catalysis, [4] memristors, [5] magnetic storage devices, [6] spintronics, [7] advanced fuel cells, [8] optoelectronics [9] and others. A natural question to ask is why these materials are not widely used yet?…”
Section: Introductionmentioning
confidence: 99%
“…PPCs are promising candidates for potential applications in spintronics and future magnetic storage devices. [6][7]49] Cho et al [49] theoretically demonstrated that the chromium porphyrin network possesses a half-metallic behavior when the Cr atom spins lie in a parallel alignment. Since the Cr atoms are separated by a large distance (>8 Å), the spin coupling is small and thus their directions can be simply controlled by an external magnetic field.…”
Section: Spintronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outermost atom of these vertical dimer could generate a giant MAE as large as 100 meV and might be increased to 150 meV with the tuning of external electrical fields. These discoveries lead to a new research field of building magnetic recording devices at the atomic scale [43][44][45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%